Konsep Ketamakan Menurut Injil Lukas 12:13-21: Sebuah Analisis Perumpamaan Yesus - Margareta Ruy; Hendi Hendi (Integritas: Jurnal Teologi, 2022)
The Concept of Greed According to the Gospel Luke 12:13-21: An Analysis of Jesus' Parables. This study aims to describe the meaning of greed from Jesus' Parable of the Rich Fool. This research is the result of the interpretation of the Scriptures using the Four Layers of Meaning in the Scriptures method to find meaning in parables and then integrate them with other biblical texts and the writings of the Church Fathers. Based on the analysis of the text of Luke 12:13-21, the writer finds that greed is a dangerous disease because it can damage human virtues for the sake of eternal life. Humans must live naturally in accordance with the purpose of God creating humans. Therefore, the greed that arises from within humans comes from the wealth of the world so that it makes humans look stupid by Allah and consequently humans are poor in front of Allah.